Experimental observation and theoretical investigation of a novel Cd(ii) complex with π-hole interactions involving nitro groups1. Issue 21 (7th June 2015) - Roy, Subhadip; Bauza, Antonio; Frontera, Antonio; Banik, Rupak; Purkayastha, Atanu; Drew, Michael G. B.; Reddy, Benjaram M.; Sridhar, Balasubramanian; Das, Saroj Kr.; Das, Subrata
<x xml:space="preserve">Abstract</x> A cadmium(ii) complex, which represents a novel example of supramolecular system bearing a network of π-hole interactions, has been synthesized.